Differential diagnosis of thrombocytopenes - A. L. Melikyan; E. I. Pustovaya; E. K. Egorova; M. V. Kalinina; T. I. Kolosheynova; I. N. Subortseva; E. A. Gilyazitdinova; V. N. Dvirnyk (Онкогематология)
The article presents a systematic diagnostic approach for thrombocytopenia, as well as the results of practical implementation of thrombocytopenia diagnostic protocol in adult patients. Among 183 patients first admitted to HRC with unspecified origin thrombocytopenia, primary immune thrombocytopenia (ITP) was established only in 48 % of patients, while in 52 % of cases it was a symptom of another pathology (the ratio was 1 : 1). As a result of re-examination of 118 relapse patients with long-term history of ITP diagnosis was confirmed in 85 % of cases, in 15 % the diagnosis has been changed to a different nosology.The results show that to establish the true causes of thrombocytopenia is necessary to conduct an extensive diagnostic search according to presented protocol.Differential diagnosis between primary immune and secondary thrombocytopenia should be carried out not only in the onset of the disease, but also in the relapse of an earlier established ITP.